ANALISIS PERANCANGAN PERAWATAN MESIN FIL-2321 UNTUK MENINGKATKAN KEANDALAN DENGAN METODE RCM II DAN MVSM (STUDI KASUS PT. PETROKIMIA GRESIK) - Denta Ferdiawan (2021)
Machine reliability is important aspect because it can affect the effectiveness and efficiency of the production process to be run. So, it is necessary to have a good maintenance to increase machine reliability, reduce downtime on production machines, and save damage repair costs. PT. Petrokimia Gresik is a manufacturing company engaged in the agriculture industry and producing fertilizers, one of the machines that experienced the highest amount of downtime was the FIL-2321 engine. Using the Reliability Centered Maintenance II (RCM II) method and also Maintenance Value Stream Mapping (MVSM) can improve machine reliability after Preventive Maintenance is carried out, save maintenance costs, and also shorten the maintenance operation time. This study proved the increase in Reliability in 4 critical parts, namely the Filter Cloth part by 44%, Prewash Water Outlet part by 45%, Lubrication Tank part by 62%, and Hoist Crane part by 60%. With cost savings after Preventive Maintenance to Rp 18.132.154 for Filter Cloth parts, Prewash Water outlet parts to Rp 14.472.524, Lubrication Tank parts to Rp 10.269.018, and Hoist Crane parts to Rp 10.292.638.